Geographical contribution to International Development Cooperation: soil quality spatial analysis tools to reactivate rural economies in Sucumbíos (Ecuador) - Sánchez-Rodríguez, Esperanza; García-Martínez, Belén; Aguilar-Alba, Mónica; Gaibor, Fátima; Albán, Alexandra; Vélez-García, Enrique; Fuertes-Grábalos, Enrique (Revista de Estudios Andaluces, 2023)
This study presents the first results of a Development Cooperation project conducted in Sucumbíos (Ecuador). The strong environmental degradation of the area is mainly associated with the extraction of oil and the presence of cadmium and lead in cocoa and coffee that difficult the international commercialization of these products. It is necessary then to evaluate the state of the soil as a basis for future mitigation measures; for this, in the present work a protocol for the collection of soil, leaf and fruit samples in the study plots is designed and tested in the field. The relevant data for the study of contamination is identified and training is provided to the local professionals in charge of the project and local stakeholders. In the framework of an international cooperation project, a Territorial Information System was created in order to manage all the information collected. For this, the relevant variables of the system were identified and protocols have been generated for field sampling and data collection. A spatial database has been designed and modeled for the purpose of normalization and efficient recording of the project information that could allow future exploitation and use of the Territorial System tools. Likewise, local agents are trained in the use of this tool. In this way, it would be providing the Province with a tool for the future management of environmental and soil data allowing the statistical analysis and cartographic production made by local agents in an increasingly autonomous way.